Ambient air pollutant mixture and lung function among children in Fresno, California - Wenxin Lu; Ellen A. Eisen; Liza Lutzker; Elizabeth Noth; Tim Tyner; Fred Lurmann; S. Katharine Hammond; Stephanie Holm; John R. Balmes (PLoS ONE, 2025)
Background Ambient air pollutants such as particulate matter (PM), ozone (O 3 ), and nitrogen dioxide (NO 2 ) have been associated with lower lung function among children. However, the reported associations could be due to correlation with other pollutants. Objective We investigate the relationships between exposures to eight ambient air pollutants and children’s lung function and apply mixture analysis to identify key contributors to health effects. Methods The Children’s Health and Air Pollution Study (CHAPS) in Fresno, California, is a prospective cohort study that recruited 299 children and assessed their lung function at two visits, at approximately 7 and 9 years of age. The children’s forced expiratory volume in the first second (FEV 1 ), forced vital capacity (FVC), and FEV 1 /FVC ratio were standardized using the Global Lung Function Initiative (GLI) race-neutral calculators. We assessed the children’s average daily residential exposures to PM 2.5 , PM 10 , nitrogen oxides (NO x ), NO 2 , O 3 , carbon monoxide (CO), elemental carbon (EC), and polycyclic aromatic hydrocarbons (PAHs), during the 1-week, 1-month, 3-month, 6-month, and 12-month periods before each visit, and the 2 years between visits. We applied linear mixed-effect models and quantile-based g-computation (q-gcomp) for statistical analysis. Results The children’s exposures to the eight ambient air pollutants exhibited high intercorrelation: Seven air pollutants were positively correlated, while O 3 exposures were negatively correlated with the other pollutants. Higher PM 10 was associated with lower FEV 1 and FEV 1 /FVC ratio, and the associations were strongest for the 3-month exposure timeframe. Q-gcomp also identified PM 10 as the key pollutant associated with lower FEV 1 and FEV 1 /FVC ratio. Conclusion Among the eight ambient air pollutants, PM 10 was the strongest risk factor for impaired lung function among children in Fresno. Ambient air pollution levels in this community exceed regulatory standards and are harmful to children’s lung function.